Analysis and Optimization of 4G LTE Network in Jombang City East Java - Widyasmoro, Widyasmoro; Chamim, Anna Nur Nazilah; Wiyagi, Rama Okta; Izmi, Rizkinanda Muhammad; Jusman, Yessi (Journal of Electrical Technology UMY, 2019)
The development of communication technology in Indonesia is currently growing, one of which is cellular telecommunications technology. Cellular communication technology developed from the first generation to the present time has entered the 4th generation known as 4G LTE. The writing of this final project discusses the analysis and optimization of the 4G LTE network of Telkomsel seluer operators in Jombang, East Java. Measurements were made using the drive test method to test the 4G LTE network in the inner area of Jombang district. This testing is done to check the network in the inner area whether it is optimal in providing network to customers. This drive test uses a nemo handy device and to analyze drive test results using a nemo analyzer. The results measured when doing a drive test are RSRP, SNR, and throughput parameters. The results of the RSRP parameter get 95% of the total sample RSRP values -100 dBm to 0 dBm. The SNR parameter gets 94% of the total sample which has a value of 0 dB to 25 dB. The throughput parameter gets 95% of the total sample value above 1Mbps. After a drive test and analysis there are 4 areas that need to be optimized because in terms of quality or SNR and the data speed or throughput is below the standards applied by the operator.